IMPLEMENTATION OF MUROTTAL AL-QURAN THERAPY FOR AUTISTIC CHILDREN (STUDY LIVING QUR'AN IN AINUL YAKIN PESANTREN FOR SPECIAL CHILDREN GUNUNG KIDUL YOGYAKARTA) - Mahmud Rifaannudin; Kartika Cahyaningtyas (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
The Qur'an is a shifa (antidote) to various diseases. The Qur'an can be one of the non-pharmacological therapies that can help cure autistic children, by listening to the murottal Qur'an. This therapy stimulate delta waves that cause the listener to be calm, and comfortable. This therapy has been practiced at the Ainul Yakin Pesantren for Special Children in Gunung Kidul, Yogyakarta. These students consist of students with special needs, ODGJ students, rehabilitation students, and independent students. This therapy is applied to autistic children, who are hyperactive, unruly, temperamental, also those with difficulty in communication, shout, speak harshly, and have difficulty concentrating and understanding lessons.